The role of the kindergarten teacher in the development of the child’s eco-aesthetic sense Field study in Lattakia City - ياسين أمل; بشرى شريبه (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The objective of the present research is to know the role of the kindergarten teacher in the development of the child’s environmental aesthetic in Lattakia city, and to define the difference between them according to the scientific qualification variable (university and higher bachelor’s degree, less than university bachelor’s degree). The researcher followed the descriptive curriculum to fit the research’s objectives. The researcher prepared a three-dimensional questionnaire for environmental aesthetic sense related to (constructive environment, natural environment, hygiene and arrangement). The questionnaire was applied to a sample of kindergarten teachers (95) selected as a simple random method. The results confirmed that the degree of exercise of the kindergarten teacher’s role in the development of the environmental aesthetic sense of the child was moderate and that there were significant differences in favors of teachers holding a university degree and more.